Policies and urban planning in small and medium-sized towns in Germany and France - Peter Dehne; Jens Hoffmann; Hélène Roth; Hélène Mainet (Cities and metropolises in France and Germany, 2022)
Quite apart from the diversity of situations in small and medium-sized towns, stabilising their town centres is a major challenge. In both countries, town centres have been weakened by commercial changes, a decline in the supply of services and transformations in lifestyles. They are characterised by an increase in vacancy rates, which accelerates a spiralling loss of attractiveness and atmosphere of neglect. Since the beginning of the 2000s, this challenge has been central in the public debate. In both countries, urban renewal has been a key element of this revitalisation policy. However, although the context of public action is rather similar in France and Germany, the modes of governance differ. In France the administrative municipal system continues to provide a narrow and fixed framework despite recent territorial reforms that favour the intermunicipal level. In addition, cooperation, communication and participation of local actors from business and civil society are more firmly anchored in social and political practice in German small and medium-sized towns.
urn:nbn:de:0156-1119068; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Town-centre decline; urban renewal; public action; local governance; small and medium-sized towns